(untitled) (Tanzania Journal for Population studies and Development, 2022)
This study provides an understanding on the impact of humanitarian interventions on the wellbeing of youth in Kasulu District, in Tanzania. Both qualitative and quantitative methods were used to collect data from respondents who included youth, parents/caretakers, officials and youth leaders in the Nyarugusu Refugee Camp and adjacent communities in Herushingo and Makere wards, who acted as the control groups. The results show that humanitarian interventions on the wellbeing of youth are vivid in the district because greater transformation was observed among some youths. However, a growing vulnerability among a larger majority was equally observed. This vulnerability was caused by outdated refugee acts, poor coordination of interventions and parenting among refugees and the host community. The study recommends improvement in coordination and matching interventions to cope with changing vulnerabilities and the needs of youths born and living in the district. Also, balance should be maintained between the active roles among youths and humanitarian actors through planning and implementation of projects, as well as promoting self-reliance for sustainable resilience among the youth. Equally, the study recommends that the Refugee Act of 1998 be amended to provide special immunities to refugee youths born in the country.